1983
DOI: 10.1002/aic.690290506
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of activated carbon. Part I: Thermal decomposition of adsorbed sodium dodecylbenzene sulfonate

Abstract: Equilibrium adsorption isotherms and rates of thermal decomposition were measured for sodium dodecyl-benzene sulfonate (DBS) adsorbed on powdered activation carbon. The rate data were obtained in a thermal gravimetric apparatus operated both at constant temperature (522 to 666 K) and with a constant rate of temperature increase from 298 to 1023 K.About 50% of the adsorbed material could be removed at temperatures up to 748 K and only a small amount of the remaining 50% could be eliminated by further heating to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1984
1984
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 5 publications
1
3
0
Order By: Relevance
“…Thus, the sodium salts increased the rate twwthree fold, but the separate effects on the residue and on the base carbon were not determined. A similar effect of sodium sulfate on the gasification rate was noted by Umehara et al (1983b). Chemisorption measurements at 240-300°C for the sodium-containing residue showed a severalfold increase in adsorption rate over the base carbon and a slightly lower activation energy of 10 kcal/mol.…”
Section: Catalytic Effectssupporting
confidence: 73%
“…Thus, the sodium salts increased the rate twwthree fold, but the separate effects on the residue and on the base carbon were not determined. A similar effect of sodium sulfate on the gasification rate was noted by Umehara et al (1983b). Chemisorption measurements at 240-300°C for the sodium-containing residue showed a severalfold increase in adsorption rate over the base carbon and a slightly lower activation energy of 10 kcal/mol.…”
Section: Catalytic Effectssupporting
confidence: 73%
“…The results showed that glycerol can be completely decomposed at a relative low temperature of 290.8 °C, 59 while the decomposition of SDBS requires a much higher temperature. 60 No thermal decomposition happens for SDBS below 217 °C. Even at a high temperature of 800 °C, 40% of SDBS is still not decomposed.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Employing thermogravimetric analysis, the thermal decomposition of SDBS and glycerol has been investigated previously. The results showed that glycerol can be completely decomposed at a relative low temperature of 290.8 °C, while the decomposition of SDBS requires a much higher temperature . No thermal decomposition happens for SDBS below 217 °C.…”
Section: Resultsmentioning
confidence: 99%
“…"After drying at 150 °C for 3 h. sucrose and sodium decylbenzenesulfonate desorption in nitrogen were examined by Chibara et al (1981) and Umehara et al (1983), respectively. A two-step decomposition, which was first-order in the adsorbates, provided a good description of the observed TGA weight losses.…”
mentioning
confidence: 99%